2011
DOI: 10.1111/j.1467-8535.2010.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning from games: Does collaboration help?

Abstract: This paper examines whether people benefit more from playing a commercial off-theshelf game in pairs rather than in solitary mode. The basic idea behind this didactic method is that there is a serious risk that solitary game play yields insufficient articulation and explanation for learning to take place. Participants in the experimental condition played a strategy game in collaborative mode (pairs). Solitary play formed the control condition. During game play data were gathered about engagement (ie, flow). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 26 publications
(28 reference statements)
2
37
1
Order By: Relevance
“…A very large majority, 90.2%, of the dialogic acts in the control condition consisted of first‐ and second‐level verbalisations. This outcome is comparable to the score of 88% found for these verbalisations by van der Meij, Albers and Leemkuil (). Likewise, the proportions of third‐ and fourth‐level verbalisations in the control group were comparable across studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A very large majority, 90.2%, of the dialogic acts in the control condition consisted of first‐ and second‐level verbalisations. This outcome is comparable to the score of 88% found for these verbalisations by van der Meij, Albers and Leemkuil (). Likewise, the proportions of third‐ and fourth‐level verbalisations in the control group were comparable across studies.…”
Section: Discussionsupporting
confidence: 88%
“…The dialogues were recorded, transcribed and coded in the same way as in the study by van der Meij, Albers and Leemkuil (2011). More specifically, we employed the same dialogue coding scheme 464 British Journal of Educational Technology Vol 51 No 2 2020 that was used in the aforementioned study (see Table 1).…”
Section: Research Instrumentsmentioning
confidence: 99%
“…It is an interesting result that most of the students emphasized the requirement of collaboration in debriefing sessions whether they were in the team debriefing group or not. Although Van der Meij et al (2011) and Van der Meij et al (2013) could not find any advantages of team debriefing, the discrepancy can be due to the game type (social game vs. individual game). Although the results showed the superiority of team debriefing, several learners preferred individual debriefing.…”
Section: Discussionmentioning
confidence: 99%
“…They have been around since at least the 1950s, and their applications in education are well-documented [De Gloria et al 2014] 1 . Collaborative serious games, in particular, combine the advantages of serious games with social learning, and some studies have suggested that they support learners in articulating the knowledge that would otherwise have remained intuitive [van der Meij et al 2011]. Although some researchers questioned the effectiveness of collaborative serious games, research in this area is still scarce and often ambiguous [Wouters et al 2013].…”
Section: Introductionmentioning
confidence: 99%